Nanometer silicon filled microcrystalline graphite negative electrode material and preparation method and application thereof
By deposition of nanosilicon in microcrystalline graphite and forming a core-shell structure, the volume expansion problem of silicon negative electrode material in lithium-ion batteries is solved, the circulation performance and energy density of the battery are improved, and more stable electrochemical performance is achieved.
Patent Information
- Application Number
- CN202411389504.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-03
AI Technical Summary
The volume expansion of the silicon negative electrode material during charging leads to cracking and powdering, thereby increasing the internal resistance and capacity attenuation of the battery. The existing silicon-carbon composite material structure is limited in circulation performance, especially the interface between graphite and silicon. The binding force is weak, making it difficult to control the volume expansion of silicon particles.
Microcrystalline graphite is used as the matrix material, nanosilicon is deposited in the grain gap of microcrystalline graphite by gradient heating method, and a porous carbon cladding layer is formed on the surface of nanosilicon filled with the microcrystalline graphite composite material to form a core-shell structure to suppress Volume expansion of silicon particles and improve conductivity.
The nano-silicon filled microcrystalline graphite negative electrode material with stable structure, high capacity and cycle stability is achieved, which reduces the expansion rate of silicon particles during charging and discharging, and improves the energy density and electrochemical properties of the material.
Smart Images

Figure CN119240689A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials for lithium batteries, and in particular to a nano-silicon filled microcrystalline graphite negative electrode material and a preparation method and application thereof. Background Art
[0002] As an energy storage device, lithium-ion batteries are widely used in various fields, such as electronic products, energy storage base stations, electric vehicles, etc., and are currently the most widely used energy storage devices. However, with the development of society and the continuous innovation of science and technology, people have higher and higher requirements for the energy storage performance of lithium-ion batteries, and are eager to have lithium-ion batteries with higher energy density and longer life.
[0003] Silicon can be used as a negative electrode material for lithium-ion batteries. It can combine with lithium ions to obtain a negative electrode material with the largest theoretical specific capacity (4200mAh·g-1), far exceeding traditional graphite (372mAh·g-1). 1 ) negative electrode material is more than ten times that of graphite, so using silicon as the negative electrode material can greatly improve the energy density of lithium-ion batteries. In addition, the charging platform of silicon is slightly higher than that of graphite, the possibility of lithium precipitation is smaller, and the safety is better than graphite. More importantly, silicon is one of the most abundant elements in the earth's crust, with a wide source and low price. Therefore, silicon negative electrode materials have broad application prospects in the field of lithium-ion power batteries. However, the volume expansion rate of the silicon negative electrode caused by the alloying of silicon and lithium during charging is as high as 400%, which can easily lead to cracking and pulverization of the silicon negative electrode, causing the internal resistance of the battery to increase rapidly. In addition, the continuous expansion and contraction of the silicon negative electrode causes the solid electrolyte interface film (SEI film) to be frequently destroyed and rebuilt, consuming a large amount of lithium ions and electrolytes, and the battery capacity decays rapidly. The above technical problems lead to reduced battery cycle performance, which in turn limits its commercial promotion and application.
[0004] In view of the above problems, the commonly used solutions are to nano-size silicon and to compound silicon with carbon. Using graphite as a matrix and loading silicon-based materials can not only reduce the volume change of negative electrode materials, but also solve the problem of poor conductivity of silicon-based materials. However, although the existing silicon-carbon composite material structure has slightly improved the cycle performance, it is relatively limited. The key problem is that the interface bonding force between graphite and silicon is weak, and the volume expansion of silicon particles on the graphite surface along the graphite sheet direction is difficult to control. Based on this, the prior art uses chemical vapor deposition to deposit silicon so that the silicon source is deposited in the porous structure of porous carbon. For example, the porous carbon and its preparation method, silicon-carbon negative electrode material, and the preparation method of silicon-carbon negative electrode material disclosed in Chinese invention patent CN1 17776183A first heat-treat the biochar to obtain a porous carbon crude product, and then use a vapor deposition method to introduce the organic carbon source into the voids of the porous carbon crude product for sealing treatment, and close the tiny pores (especially pores below 1 nm) in the 1nm porous carbon. The reason is that the tiny pores (especially pores below 1 nm) cannot contribute to the silane vapor deposition, that is, silane cannot enter the tiny voids, and a large number of micropores below 1 nm will cause the porous carbon to have too high a specific surface area, affecting the mechanical properties and mechanical parameters of the silicon-carbon negative electrode material; finally, the silane gas is deposited by vapor deposition.
[0005] On the other hand, when microcrystalline graphite is used as a matrix material, the average interlayer spacing of microcrystalline graphite that can be used as a negative electrode material for lithium-ion batteries is between 0.335-0.337nm, and the grain gap of the microcrystals is between 0.1nm and 2μm. The structural characteristics of microcrystalline graphite make the grain gaps of microcrystalline graphite different in size. In particular, the interior contains a large number of tiny grain gaps of less than 1nm. It is almost impossible to complete the uniform filling of silane between the grain gaps using conventional silane vapor deposition method for silane deposition.
[0006] In view of this, the present invention provides a method for preparing a nano-silicon filled microcrystalline graphite negative electrode material, wherein microcrystalline graphite is selected as a matrix material, and nano-silicon is filled between the grains of the microcrystalline graphite. The volume expansion of silicon particles is suppressed by taking advantage of the structural characteristics that the grain structure of the microcrystalline graphite has different orientations and there are a large number of gaps between the grains. At the same time, silane filling can be achieved in the grain gaps of the microcrystalline graphite, including gaps below 1 nm. Summary of the invention
[0007] The invention provides a nano-silicon filled microcrystalline graphite negative electrode material and a preparation method and application thereof; the prepared microcrystalline graphite negative electrode material has the advantages of stable structure, high capacity and good cycle stability.
[0008] In order to achieve the above-mentioned purpose, the present invention provides a method for preparing a nano-silicon filled microcrystalline graphite negative electrode material, which uses microcrystalline graphite as a matrix material, and adopts a gradient temperature rising method to deposit silane between the grains of microcrystalline graphite to obtain a nano-silicon filled microcrystalline graphite composite material; finally, a carbon source is coated on the surface of the nano-silicon filled microcrystalline graphite composite material and carbonized to form a porous structure on the surface of the nano-silicon filled microcrystalline graphite composite material, thereby forming a nano-silicon filled microcrystalline graphite negative electrode material with a core-shell structure.
[0009] Preferably, the gradient temperature increase method includes heating in a first stage and heating in a second stage.
[0010] Specifically, the first stage of heating includes introducing silane gas under high pressure, heating to a first temperature at a first heating rate, and then stopping the ventilation.
[0011] The second stage of heating includes introducing an inert gas under normal pressure, heating to a second temperature at a second heating rate, and cooling to room temperature after keeping the temperature.
[0012] Preferably, the second temperature is higher than the first temperature.
[0013] Preferably, the first heating rate is higher than the second heating rate.
[0014] More preferably, in the first stage, the high pressure condition includes a pressure of 3.3-3.8 MPa.
[0015] More preferably, the first heating rate is 8-15° C. / min.
[0016] More preferably, the first temperature is 380-420°C.
[0017] More preferably, the second heating rate is 2-6°C / min.
[0018] More preferably, the second temperature is 450-500°C.
[0019] More preferably, the insulation time is 1 to 2 hours.
[0020] Specifically, the method for preparing the nano-silicon filled microcrystalline graphite negative electrode material provided by the present invention comprises the following steps:
[0021] S1. Silicon source filling: Place microcrystalline graphite particles in a tube furnace, adjust the pressure in the furnace to 2-4 MPa, then introduce inert gas to exhaust, and finally introduce silane gas for 15-20 minutes;
[0022] S2. Silicon deposition: using the gradient temperature rise method, closing the gas outlet valve, introducing silane gas under high pressure, and raising the temperature to a first temperature; then, opening the gas outlet valve, restoring the tubular furnace to a normal pressure state, and introducing an inert gas for 3 to 5 minutes, while raising the temperature to a second temperature, keeping the temperature for 1 to 2 hours, and then cooling to room temperature; finally, obtaining a nano-silicon filled microcrystalline graphite composite material;
[0023] S3. Coating carbonization: adding a carbon source precursor to the nano-silicon filled microcrystalline graphite composite material, mixing evenly, and then carbonizing in an inert gas or nitrogen atmosphere to obtain a nano-silicon filled microcrystalline graphite negative electrode material.
[0024] Preferably, in S1, the carbon content of the microcrystalline graphite particles is ≥ 99.5%, D 50 =8~18μm, tap density is 0.5~1g / cc, specific surface area is 5~15m 2 / g.
[0025] Preferably, the exhaust comprises introducing an inert gas or nitrogen for 15 to 30 minutes.
[0026] Preferably, the flow rate of the inert gas and / or silane gas is 0.8-1.2 L / min.
[0027] Preferably, in S2, the flow rate of the silane gas is 0.1-0.2 L / min, and the flow rate of the inert gas is 0.2-0.4 L / min; the role of the inert gas in the second heating stage also includes removing the unreacted silane on the surface of the microcrystalline graphite.
[0028] Preferably, S2 is repeated at least twice so that the silicon particles can be fully filled in the gaps of the microcrystalline graphite.
[0029] More preferably, S2 is repeated 2 to 3 times.
[0030] Preferably, in S1 and S2, the inert gas is argon.
[0031] Preferably, in S3, the organic carbon includes any one or a combination of two or more of petroleum coke, asphalt compounds, polyacrylonitrile, phenolic resin, epoxy resin, mesophase asphalt fiber, and lignin.
[0032] As another object of the invention, the present invention also provides a nano-silicon filled microcrystalline graphite negative electrode material, which is obtained by the above-mentioned preparation method.
[0033] Preferably, the nano-silicon filled microcrystalline graphite negative electrode material has a core-shell structure; the core is a nano-silicon filled microcrystalline graphite composite material, and the nano-silicon particles are filled in the gaps between the microcrystalline graphite flakes; the shell is a carbon coating layer with a porous structure; the carbon coating layer wraps the surface of the nano-silicon filled microcrystalline graphite composite material.
[0034] Preferably, the mass percentage of the core to the mass percentage of the nano-silicon filled microcrystalline graphite negative electrode material is 92-97%.
[0035] Furthermore, the mass percentage content of silicon in the nano-silicon filled microcrystalline graphite composite material is 5-15%.
[0036] Beneficial technical effects obtained by the present invention:
[0037] 1. The nano-silicon filled microcrystalline graphite negative electrode material provided by the present invention has a core-shell structure, wherein the core is a silicon-graphite composite material formed by nano-silicon filling microcrystalline graphite, and the nano-silicon particles are filled on the surface and gaps of the microcrystalline graphite grains, and the shell is a carbon coating layer with a porous structure, which is wrapped on the surface of the nano-silicon filled microcrystalline graphite composite material. The volume expansion of the nano-silicon during the charge and discharge process is suppressed by the microcrystalline graphite matrix material, and in particular, the volume expansion of the microcrystalline graphite can be further suppressed due to the different structural orientations of the stress-induced material.
[0038] 2. The technical solution of the present invention uses microcrystalline graphite as the matrix material, and the nano-silicon particles filled in the gaps of the microcrystalline graphite flake layer also provide a three-dimensional conductive network structure for the silicon particles, solving the problem of poor electrical conductivity of the silicon particles; at the same time, the silicon particles filled in the gaps of the microcrystalline graphite can also improve the energy density, true density and tap density of the material, thereby solving the defect of low specific capacity of graphite.
[0039] 3. The technical solution of the present invention is used to fill nano-silicon in the gaps between the grains of microcrystalline graphite. There is a certain amount of free space in the gaps, so that the negative electrode material has a volume self-absorption effect on the expansion of silicon during the charging and discharging process, which greatly reduces the expansion effect of silicon, thereby reducing the expansion rate of the electrode during the charging and discharging process, ensuring good electrical contact between the active substances, and reducing the rupture and repair of the SEI film due to the expansion of the electrode. Therefore, the graphene-based silicon-carbon composite negative electrode material provided by the present invention has excellent cycle performance.
[0040] 4. By adopting the technical solution of the present invention, the gaps between the sheets of microcrystalline graphite are different from the pore structure of porous carbon in the prior art. The silicon filling of porous carbon is silicon particles filling the pore structure of porous carbon. During the recycling of negative electrode materials, the repeated expansion of silicon causes the silicon particles to fall off, thereby causing the attenuation of negative electrode materials. In order to prevent this phenomenon, it is usually necessary to seal the voids. The relative space between the sheets of microcrystalline graphite in the present invention is smaller than the pore structure of porous carbon. At the same time, due to the chaotic layer structure of microcrystalline graphite, after nano-silicon is filled into the gap, it completely forms an integral structure with the microcrystalline graphite, and can also provide a certain amount of free space for silicon expansion. In particular, the pore structure of microcrystalline graphite is a natural structure, which does not require pore-making treatment, thereby simplifying the process steps.
[0041] 5. The nano-silicon filled microcrystalline graphite negative electrode material provided by the present invention is different from the traditional silicon-graphite negative electrode material. The silicon particles are distributed neither on the surface of the graphite particles nor in the pore structure of the graphite material, but are filled in the gaps between the microcrystalline graphite grains, so there is no need to make pores or modify the surface of the graphite; moreover, the outer carbon coating layer wrapped in the nano-silicon filled microcrystalline graphite composite material can further stabilize the microcrystalline graphite, thereby forming an integrated core-shell structure, further improving the cycle performance of the negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a SEM image of a cross section of the microcrystalline graphite matrix material used in Example 1 of the present invention.
[0043] Figure 2 This is a SEM image of a cross section of the nano-silicon filled microcrystalline graphite composite material prepared in Example 1 of the present invention.
[0044] Figure 3 This is the first charge and discharge curve of a button cell assembled with the nano-silicon filled microcrystalline graphite composite material as the negative electrode material according to Example 1 of the present invention. DETAILED DESCRIPTION
[0045] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below in combination with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments.
[0046] The present invention provides a method for preparing a nano-silicon filled microcrystalline graphite negative electrode material. The method comprises the following steps: using microcrystalline graphite as a matrix material, depositing silane between crystal grains of the microcrystalline graphite by a gradient temperature rise method, and obtaining a nano-silicon filled microcrystalline graphite composite material; finally, coating the surface of the nano-silicon filled microcrystalline graphite composite material with a carbon source and carbonizing the carbon source, forming a porous structure on the surface of the nano-silicon filled microcrystalline graphite composite material, and further forming a nano-silicon filled microcrystalline graphite negative electrode material with a core-shell structure.
[0047] The technical solution of the present invention is described in detail below through specific embodiments.
[0048] Example 1
[0049] This embodiment provides a method for preparing a nano-silicon filled microcrystalline graphite negative electrode material, and the specific preparation steps include:
[0050] S1. Silicon source filling: Place microcrystalline graphite particles in a tube furnace, adjust the pressure in the furnace to 2.5 MPa, then introduce nitrogen gas for exhaust for 15 minutes at a gas flow rate of 0.8 L / min, and finally introduce monosilane gas for 15 minutes at a gas flow rate of 0.1 L / min;
[0051] Among them, the carbon content of the selected microcrystalline graphite particles is 99.653%, D 50 =11.3μm, tap density is 0.856g / cc, specific surface area is 6.469m 2 / g.
[0052] S2. Silicon deposition: using the gradient heating method, first, close the outlet valve, introduce monosilane gas, the gas flow rate is 0.2L / min, the pressure in the furnace reaches 3.4MPa, and the temperature is increased to 380℃ at 10℃ / min; then, open the outlet valve, restore the tubular furnace to normal pressure, introduce nitrogen for 3min, and at the same time, increase the temperature to 450℃ at 6℃ / min, keep warm for 1h and then cool to room temperature; repeat the above steps twice to finally obtain nano-silicon filled microcrystalline graphite composite materials.
[0053] S3. Coating carbonization: Add 6% mesophase asphalt to the nano-silicon filled microcrystalline graphite composite material, mix well, and carbonize at 1150-1250° C. for 3-6 hours in an argon atmosphere to obtain a nano-silicon filled microcrystalline graphite negative electrode material.
[0054] Nano-silicon filled microcrystalline graphite negative electrode material was prepared into button cells and the electrochemical performance was tested.
[0055] See also Figure 1, is a SEM image of the cross section of the microcrystalline graphite matrix material used in S1 in this embodiment. It can be seen from the figure that there are a large number of nano-scale and micron-scale gaps between the grains of the microcrystalline graphite, and the size of the gaps is between 0.1nm and 2μm.
[0056] See also Figure 2 , is the SEM image of the cross section of the nano-silicon filled microcrystalline graphite composite material obtained by S2 after silicon deposition, and Figure 1 In comparison, the original voids in the microcrystalline graphite are almost completely filled, indicating that the technical solution of the present invention can achieve complete filling of silane.
[0057] See also Figure 3 , which is the first charge and discharge curve of the button cell with the nano-silicon filled microcrystalline graphite composite material as the negative electrode material of this embodiment; see Table 1 for specific results, the first charge specific capacity is 540.81 mAh / g, the first coulombic efficiency is 89.53%, the 3C lithium removal capacity retention rate is 93.3%, and the 3C lithium insertion capacity retention rate is 88.7%.
[0058] Example 2
[0059] This embodiment provides a method for preparing a nano-silicon filled microcrystalline graphite negative electrode material, and the specific preparation steps include:
[0060] S1. Silicon source filling: Place the microcrystalline graphite particles in a tube furnace, adjust the furnace pressure to 3Mpa, then introduce nitrogen to exhaust for 15 minutes, the gas flow rate is 0.8L / min, and finally introduce monosilane gas for 15 minutes, the gas flow rate is 0.1L / min; the carbon content of the microcrystalline graphite matrix material is 99.990%, D 50 =16.5μm, tap density is 0.898g / cc, specific surface area is 5.946m 2 / g.
[0061] S2. Silicon deposition: adopt the gradient heating method, close the outlet valve, introduce monosilane gas, the gas flow rate is 0.2L / min, the pressure in the furnace reaches 3.6MPa, and the temperature is increased to 400℃ at 15℃ / min; then, open the outlet valve, restore the tubular furnace to normal pressure, introduce nitrogen for 5 minutes, and at the same time increase the temperature to 500℃ at 6℃ / min, keep warm for 1h and then cool to room temperature; repeat the above steps 3 times to finally obtain nano-silicon filled microcrystalline graphite composite materials.
[0062] S3. Coating carbonization: adding 10% of mesophase asphalt to the nano-silicon filled microcrystalline graphite composite material, mixing evenly, and then carbonizing under an inert gas atmosphere to obtain a nano-silicon filled microcrystalline graphite negative electrode material.
[0063] The electrochemical performance of the nano-silicon filled microcrystalline graphite negative electrode material was tested, with the first charge specific capacity being 645.09 mAh / g, the first coulombic efficiency being 90.56%, the 3C lithium removal capacity retention rate being 94.7%, and the 3C lithium insertion capacity retention rate being 90.1%.
[0064] Example 3
[0065] This embodiment provides a method for preparing a nano-silicon filled microcrystalline graphite negative electrode material, and the specific preparation steps include:
[0066] S1. Silicon source filling: Place the microcrystalline graphite particles in a tube furnace, adjust the pressure in the furnace to 2Mpa, then introduce nitrogen to exhaust for 15 minutes, the gas flow rate is 0.8L / min, and finally introduce disilane gas for 20 minutes, the gas flow rate is 0.1L / min; the carbon content of the microcrystalline graphite particles is 99.675%, D 50 =14.5μm, tap density is 0.831g / cc, specific surface area is 5.211m 2 / g.
[0067] S2. Silicon deposition: using the gradient temperature rise method, closing the gas outlet valve, introducing monosilane gas, the pressure in the furnace is 3.5MPa, and the temperature is raised to 380°C at 8°C / min; then, opening the gas outlet valve, returning the tubular furnace to normal pressure, introducing nitrogen for 5 minutes, and at the same time raising the temperature to 450°C at 2°C / min, keeping the temperature for 1 hour, and then cooling to room temperature; repeating the above steps twice to finally obtain a nano-silicon filled microcrystalline graphite composite material;
[0068] S3. Coating carbonization: adding 12% of mesophase asphalt to the nano-silicon filled microcrystalline graphite composite material, mixing evenly, and then carbonizing under an inert gas atmosphere to obtain a nano-silicon filled microcrystalline graphite negative electrode material.
[0069] The electrochemical performance of the nano-silicon filled microcrystalline graphite negative electrode material was tested, with the first charge specific capacity being 607.81 mAh / g, the first coulombic efficiency being 90.83%, the 3C lithium removal capacity retention rate being 95.0%, and the 3C lithium insertion capacity retention rate being 90.5%.
[0070] Example 4
[0071] The difference between this embodiment and embodiment 2 lies in the silicon deposition step of S2. The above steps are repeated 4 times to finally obtain a nano-silicon filled microcrystalline graphite composite material.
[0072] The electrochemical performance of the microcrystalline graphite negative electrode material filled with nano-silicon was tested, and the results were similar to those in Example 2, which showed that the nano-silicon could achieve good filling by repeating this step 2 to 3 times.
[0073] Example 5
[0074] The difference between this embodiment and embodiment 1 lies in the silicon source filling of S1: the microcrystalline graphite particles are placed in a tubular furnace, the pressure in the furnace is adjusted to 2.5 MPa, and then nitrogen is introduced to exhaust for 15 minutes with a gas flow rate of 0.8 L / min, and finally monosilane gas is introduced for 15 minutes with a gas flow rate of 0.2 L / min. Other conditions are the same as those in embodiment 2.
[0075] Comparative Example 1
[0076] This comparative example provides a graphite negative electrode material and a preparation method thereof, which differs from Example 2 in that: in S2, the gas outlet valve is kept open during the silicon deposition process so that the furnace is always kept at normal pressure, and other conditions are consistent with Example 2.
[0077] Comparative Example 2
[0078] The preparation method of the graphite negative electrode material provided in this comparative example is different from that in Example 1 in that in S2, the silicon deposition process is not repeated after cooling to room temperature, that is, silicon deposition is performed only once, and other conditions are consistent with Example 1.
[0079] Comparative Example 3
[0080] The graphite negative electrode material and preparation method thereof provided in this comparative example are different from those in Example 1 only in that: in S2 of this comparative example, a gradient temperature rise method is adopted. First, the gas outlet valve is closed, and monosilane gas is introduced with a gas flow rate of 0.2 L / min. The pressure in the furnace is increased to 3.4 MPa, and the temperature is increased to 380°C at 10°C / min; then, the gas outlet valve is opened, the tubular furnace is restored to normal pressure, and nitrogen is introduced for 3 minutes. At the same time, the temperature is increased to 440°C at 6°C / min, and the temperature is kept for 1 hour and then cooled to room temperature; the above steps are repeated twice to finally obtain a nano-silicon filled microcrystalline graphite composite material.
[0081] Other conditions are consistent with those in Example 1.
[0082] Comparative Example 4
[0083] The preparation method of the graphite negative electrode material provided in this comparative example is different from that in Example 1 as follows: In S2 of this comparative example, a gradient temperature rise method is adopted. First, the gas outlet valve is closed, and monosilane gas is introduced with a gas flow rate of 0.2 L / min. The pressure in the furnace is increased to 3.4 MPa, and the temperature is increased to 380°C at 10°C / min; then, the gas outlet valve is opened, the tubular furnace is restored to normal pressure, and nitrogen is introduced for 3 minutes. At the same time, the temperature is increased to 510°C at 6°C / min, and the temperature is kept for 1 hour and then cooled to room temperature; the above steps are repeated twice to finally obtain a nano-silicon filled microcrystalline graphite composite material.
[0084] Other conditions are consistent with those in Example 1.
[0085] Comparative Example 5
[0086] The preparation method of the graphite negative electrode material provided in this comparative example is different from that in Example 1 as follows: In S2 of this comparative example, a gradient temperature rise method is adopted. First, the gas outlet valve is closed, and monosilane gas is introduced with a gas flow rate of 0.2 L / min. The pressure in the furnace is increased to 3.4 MPa, and the temperature is increased to 450°C at 10°C / min; then, the gas outlet valve is opened, the pressure in the tubular furnace is restored to normal pressure, and nitrogen is introduced for 3 minutes. At the same time, the temperature is increased to 450°C at 6°C / min, and the temperature is kept for 1 hour and then cooled to room temperature; the above steps are repeated twice to finally obtain a nano-silicon filled microcrystalline graphite composite material.
[0087] Other conditions are consistent with those in Example 1.
[0088] Comparative Example 6
[0089] The preparation method of the graphite negative electrode material provided in this comparative example is different from that in Example 1 as follows: In S2 of this comparative example, a gradient temperature rise method is adopted. First, the gas outlet valve is closed, and monosilane gas is introduced with a gas flow rate of 0.2 L / min. The pressure in the furnace is increased to 3.4 MPa, and the temperature is increased to 380°C at 6°C / min; then, the gas outlet valve is opened, the tubular furnace is restored to normal pressure, and nitrogen is introduced for 3 minutes. At the same time, the temperature is increased to 450°C at 6°C / min, and the temperature is kept for 1 hour and then cooled to room temperature; the above steps are repeated twice to finally obtain a nano-silicon filled microcrystalline graphite composite material.
[0090] Other conditions are consistent with those in Example 1.
[0091] Comparative Example 7
[0092] The preparation method of the graphite negative electrode material provided in this comparative example is different from that in Example 1 in that the silicon source filling of S1 is as follows: the microcrystalline graphite particles are placed in a tubular furnace, the pressure in the furnace is adjusted to 2.5 MPa, and then nitrogen is introduced to exhaust for 15 minutes, and the gas flow rate is 0.8 L / min, and finally monosilane gas is introduced for 15 minutes, and the gas flow rate is 0.3 L / min. The other conditions are the same as those in Example 2.
[0093] Comparative Example 8
[0094] The preparation method of the graphite negative electrode material provided in this comparative example is different from that in Example 1 in that the silicon source filling of S1 is as follows: the microcrystalline graphite particles are placed in a tubular furnace, the pressure in the furnace is adjusted to 2.5 MPa, and then nitrogen is introduced to exhaust for 15 minutes, and the gas flow rate is 0.8 L / min. Finally, monosilane gas is introduced for 15 minutes, and the gas flow rate is 0.08 L / min. The other conditions are the same as those in Example 2.
[0095] Comparative Example 9
[0096] The preparation method of the graphite negative electrode material provided in this comparative example is different from that in Example 2 in that in S2, the gas outlet valve is kept closed during the silicon deposition process, and the pressure in the furnace is adjusted to be maintained at 3.0 MPa, and other conditions are consistent with Example 2.
[0097] The results of the embodiments and comparative examples obtained above were tested, including specific surface area test, tap density test, true density test and electrical property test. The specific test results are shown in Table 1.
[0098] Table 1 Performance test
[0099]
[0100] It can be seen from the above experimental results that the parameters described in the scheme of the present invention can be controlled to prepare nano-silicon filled microcrystalline graphite negative electrode materials with excellent electrochemical properties. The negative electrode material has a higher specific capacity and first coulombic efficiency (or first efficiency). Nano-silicon is filled in the microcrystalline graphite matrix, which improves the tap density and true density of the material, improves the specific capacity of the microcrystalline graphite, and the microcrystalline graphite limits the volume expansion of silicon particles, thereby improving the first coulombic efficiency of the composite material. Therefore, for the technical scheme provided by the present invention, changes in tap density and electrochemical properties can also reflect the situation of silane gas filling into the graphite gap.
[0101] Further comparison was made between Example 1, Example 2, Example 4 and Comparative Example 2, and the number of repetitions of silicon deposition was compared. It was found that Comparative Example 1 did not repeat the deposition step of introducing silane gas, resulting in incomplete silicon deposition, and almost no silicon particles were filled in the gaps in some microcrystalline graphite, resulting in no obvious improvement in the capacity of the negative electrode material, and low tap density and true density; while the results of Example 2 and Example 4 were equivalent, indicating that by adopting the technical solution of the present invention, the silicon deposition step can be repeated 2 to 3 times to achieve complete filling.
[0102] Comparative Example 1, Comparative Example 9 and Example 2 respectively give silane deposition under pressure conditions during gradient heating. The results show that when silane gas is introduced into Comparative Example 1, the furnace is kept at normal pressure, resulting in the inability of silane gas to enter the gaps between microcrystalline graphite. After heating, silicon particles are deposited on the surface of microcrystalline graphite, but cannot enter the gaps between the grains of microcrystalline graphite, resulting in lower tap density, true density and first efficiency of the negative electrode material, and a larger specific surface area; and when the pressure of Comparative Example 9 is 3.0MPa, the filling effect is still poor. Obviously, due to the structural characteristics of microcrystalline graphite, conventional vapor deposition methods cannot achieve silane deposition between smaller grain gaps.
[0103] Furthermore, the present invention also compares the temperatures of each stage of gradient heating. Referring to the electrochemical test results of Example 1, Comparative Example 5 and Comparative Example 6, it can be concluded that when the second temperature should be higher than the first temperature, and / or the first heating rate is higher than the second heating rate, the deposition effect is not ideal; and Comparative Examples 3 and Comparative Examples 4 investigated the influence of the second temperature on silane deposition during gradient heating during silicon deposition, and found that when the second temperature is too low (lower than 450°C) or too high (higher than 500°C), the temperature of silane gas deposition is too low or too high, and the deposition effect is not ideal. When the deposition temperature is too low, part of the silane gas cannot be converted into silicon particles, resulting in lower material specific capacity, tap density, and true density; and when the deposition temperature is too high, the silicon deposition rate is too fast, and part of the silicon is deposited on the surface of the microcrystalline graphite, resulting in lower first coulombic efficiency and true density of the negative electrode material.
[0104] Furthermore, the present invention also compares the flow rate of monosilane gas during the gradient heating process, referring to the test results of Example 2, Example 5, Comparative Example 7 and Comparative Example 8, wherein the results of Example 5 and Comparative Example 7 are equivalent, indicating that the technical solution of the present invention can be used with a silane gas flow rate of ≤0.2L / min to meet the complete filling of silane. The results of Comparative Example 8 show that the silane gas flow rate is ≤0.1L / min, and the silane filling is incomplete, resulting in lower material specific capacity, tap density, and true density.
[0105] The present embodiment provides only the preferred embodiments of the present invention, which does not limit the protection scope of the present invention. For those skilled in the art, the present invention may have various modifications and changes. Within the spirit and principle of the present invention, the changes, modifications, replacements, integrations and parameter changes of these embodiments by conventional substitutions or by being able to achieve the same functions without departing from the principles and spirit of the present invention all fall within the protection scope of the present invention.
Claims
1. A method for preparing a nano-silicon filled microcrystalline graphite negative electrode material, characterized in that: Microcrystalline graphite is used as a matrix material, and silane is deposited between the grains of microcrystalline graphite by a gradient temperature increase method to obtain a nano-silicon filled microcrystalline graphite composite material; finally, a carbon source is coated on the surface of the nano-silicon filled microcrystalline graphite composite material and carbonized to form a porous structure on the surface of the nano-silicon filled microcrystalline graphite composite material, thereby forming a nano-silicon filled microcrystalline graphite negative electrode material with a core-shell structure.
2. The method for preparing the nano-silicon filled microcrystalline graphite negative electrode material according to claim 1, characterized in that: The gradient temperature increase method includes increasing the temperature in the first stage and increasing the temperature in the second stage; The first stage of heating includes introducing silane gas under high pressure, heating to a first temperature at a first heating rate, and then stopping the ventilation; The second stage of heating includes introducing an inert gas under normal pressure, heating to a second temperature at a second heating rate, and cooling to room temperature after keeping the temperature. wherein the second temperature is higher than the first temperature; The first heating rate is higher than the second heating rate.
3. The method for preparing the nano-silicon filled microcrystalline graphite negative electrode material according to claim 2, characterized in that: In the first stage, the high pressure condition includes a pressure of 3.3 to 3.8 MPa; The first heating rate is 8 to 15°C / min; The first temperature is 380-420° C.; In the second stage, the second heating rate is 2-6°C / min; The second temperature is 450-500° C.; The insulation time is 1 to 2 hours.
4. The method for preparing the nano-silicon filled microcrystalline graphite negative electrode material according to claim 1, characterized in that: The following steps are involved: S1. Silicon source filling: Place microcrystalline graphite particles in a tube furnace, adjust the pressure in the furnace to 2-4 MPa, then introduce protective gas for exhaust, and finally introduce silane gas; S2. Silicon deposition: using the gradient temperature rise method, closing the gas outlet valve, continuing to introduce silane gas under high pressure, and raising the temperature to the first temperature; then, opening the gas outlet valve, restoring the pressure in the tubular furnace to normal pressure, and introducing protective gas for 3 to 5 minutes, while raising the temperature to the second temperature, keeping the temperature for 1 to 2 hours, and then cooling to room temperature; finally, obtaining a nano-silicon filled microcrystalline graphite composite material; S3. Coating carbonization: adding a carbon source precursor to the nano-silicon filled microcrystalline graphite composite material, mixing evenly, and then carbonizing under an inert gas atmosphere to obtain a nano-silicon filled microcrystalline graphite negative electrode material.
5. The method for preparing the nano-silicon filled microcrystalline graphite negative electrode material according to claim 4, characterized in that: In S1, the carbon content of microcrystalline graphite particles is ≥ 99.5%, D 50 =8-18μm, tap density is 0.5-1g / cc, specific surface area is 5-15m 2 / g; The exhaust time lasts for 15 to 30 minutes; the flow rate of the protective gas is 0.8 to 1.2 L / min; The silane gas is introduced for 15 to 20 minutes at a flow rate of 0.8 to 1.2 L / min. In S2, the flow rate of the silane gas is 0.1-0.2 L / min, and the flow rate of the protective gas is 0.2-0.4 L / min; S2 is repeated at least 2 times; In S1 and S2, the protective gas is an inert gas or nitrogen; the inert gas is preferably argon.
6. The method for preparing the nano-silicon filled microcrystalline graphite negative electrode material according to claim 4, characterized in that: In S3, the carbon source precursor includes at least one of petroleum pitch, coal pitch, mesophase pitch, phenolic resin, epoxy resin, coal tar and heavy oil.
7. A nano-silicon filled microcrystalline graphite negative electrode material prepared from the nano-silicon filled microcrystalline graphite negative electrode material according to any one of claims 1 to 6.
8. The nano-silicon filled microcrystalline graphite negative electrode material according to claim 7, characterized in that: The nano-silicon filled microcrystalline graphite negative electrode material has a core-shell structure; the core is a nano-silicon filled microcrystalline graphite composite material, and the nano-silicon particles are filled in the gaps between the microcrystalline graphite flakes; the shell is a carbon coating layer with a porous structure; The carbon coating layer wraps the surface of the nano-silicon filled microcrystalline graphite composite material.
9. The nano-silicon filled microcrystalline graphite negative electrode material according to claim 8, characterized in that: The mass percentage of the core to the mass percentage of the nano-silicon filled microcrystalline graphite negative electrode material is 92N97%; The mass percentage content of silicon in the nano-silicon filled microcrystalline graphite composite material is 5N15%.
10. A lithium ion battery comprising at least the nano-silicon filled microcrystalline graphite negative electrode as claimed in claim 9.
Citation Information
Cited By
Ultrahigh-capacity spherical graphite negative electrode material and production method thereof
CN120933329A
Preparation method of pre-lithiation-free low-cost high-first-effect composite coated nano silicon
CN121617941A
Graphite composite material and preparation method thereof, negative plate, electrochemical device and electronic equipment
CN121812535A
Graphite composite material and preparation method thereof, negative plate, electrochemical device and electronic equipment
CN121812536A